Kecerdasan Emosi: Pengendalian reaksi konstruktif - Nugroho, Nihlah Alifatul Rohmah (Maliki Interdisciplinary Journal, 2025)
Emotional intelligence is the ability to recognize, understand, and manage one’s own emotions and the emotions of others. One of the main aspects of emotional intelligence is emotional control, which is important in maintaining emotional balance and achieving success in personal and professional life. Controlling emotions does not mean suppressing feelings, but rather managing emotional reactions constructively so as not to damage social relationships or decision-making. The process of emotional control includes self-awareness to recognize emerging emotions, emotional regulation to calm oneself, and the ability to respond to situations wisely. Some ways that can be done to manage emotions include relaxation techniques, reframing, and increasing empathy and social skills. Developing emotional intelligence brings great benefits, including improving interpersonal relationships, increasing work productivity, and maintaining mental health. However, controlling emotions also has challenges, especially in situations that trigger strong emotional reactions.